The intersections of selves and policies: A poetic inquiry into the hydra of teacher education - Stephanie Behm Cross; Alyssa Hadley Dunn; Erica K. Dotson (Arizona State University, 2018)
This article explores the intersection of selves and policies for teacher educators in an era of teacher education reform. Borne out of a promise to one another to write about our experiences navigating increasingly complex market-driven, neoliberal attacks on our work and world, we collected data across several years that documented our attempt to break our silence (Lorde, 1977) and explore how we, as teacher educators, make sense of neoliberal reforms and policies in teacher preparation. We draw specifically on Dunn's theory of the Hydra of Teacher Education (2016), alongside literature on reforms and policies in teacher preparation and teacher educators' forms of resistance to frame our work, and utilize arts-based poetic inquiry methodology (Prendergast, 2009; Rath, 2001) to explore the real, everyday implications of educational policy in our lives and in our careers. The poems we created as a "performative act" (Prendergast, 2009, p. xxiii) revealed that our experiences seemed to follow a cycle from hopelessness, to silence, to acquiescence, to collective resistance. We look carefully at this last portion of the cycle in our work, wondering how, if at all, teacher educators can resist the neoliberalization of teacher preparation. We conclude with implications for research, policy, and the practice of teacher education as we write to understand, write to resist, and write to survive.